The Multidimensionality of Reporting in Insurance Companies (Balance Sheet Law, Solvency II, SREP, CSO) - Spigarska , Ewa (Studia Oeconomica Posnaniensia, 2018)
Insurance companies as financial institutions draw up reports for many users. The primary responsibility of insurance companies is to prepare reports for the purpose of the accounting law, the scope of which is a direct result of the Accounting Act and International Financial Reporting Standards. Significant changes in this area should be expected after the implementation of IFRS 4 Phase II "Insurance Contracts" and IFRS 9 "Financial Instruments". In connection with the implementation of the "Solvency II" directive, insurance companies must also prepare reports on their solvency and publicly disclose them. These issues constitute the third pillar of the directive and are necessary to carry out the assessment of the management systems in force in a company by the supervisory authority. The information provided to the supervisory authority by the insurance company must meet the criteria of availability, completeness, comparability and relevance as well as credibility and intelligibility. In addition the supervisory authority under the "Supervisory Review and Evaluation Process" (SREP) on the basis of available information, performs a risk assessment in the company and a quality assessment of the risk management process of the institution. This often requires the fulfilment of additional questionnaires or surveys. Another institution which requires the preparation of appropriate reporting is the Central Statistical Office. Regardless of that insurance companies, from the point of view of the tax law are required to draw up relevant tax returns (CIT, VAT) and forward certain sheets (e.g. in the area of transfer pricing). Therefore, the aim of this article is to analyse the preparation of various reports, and to indicate the requirement challenges for insurance companies.